Implementasi Prinsip Maqāṣid al-Syarī’ah dalam Regulasi Fintech Syariah di Indonesia: Pendekatan Yuridis Normatif - Masyhadi, Ahmad; Farochi, M. Mar’il (Program Studi Hukum Ekonomi Syariah, 2025)
This study analyzes the implementation of the principles of Maqāṣid al-Syarī’ah in Islamic Fintech regulations in Indonesia through a normative juridical approach. Maqāṣid al-Syarī’ah, as the main goal of sharia, includes the protection of religion, soul, intellect, descendants, and property. This study aims to evaluate the extent to which Islamic Fintech regulations in Indonesia reflect these principles and provide solutions to improve regulatory compliance with Maqāṣid al-Syarī’ah. The normative juridical method is used to analyze relevant laws and regulations as well as related literature. The results of the study show that sharia Fintech regulations in Indonesia require compliance with the principles of Maqāṣid al-Syarī’ah in economic activities. This research provides recommendations for the development of more comprehensive regulations in accordance with sharia principles, as well as supporting the sustainable and inclusive growth of the sharia fintech industry.